Celebrity insects: Exploring the effect of celebrity endorsement on people's willingness to eat insect-based foods. (April 2022) - Park, Jaewoo; Motoki, Kosuke; Velasco, Carlos; Spence, Charles
Highlights: Celebrity endorsement represents a useful strategy for promoting insect-based foods. Endorser's perceived characteristics affect willingness to eat (WTE) insect-based foods. Celebrity type interacts with participant gender on WTE insect-based foods. Ads featuring actors/actresses or athletes are effective for males. Ads featuring actors/actresses are effective for females. Abstract: There is a growing interest in insects as a promising alternative source of protein that can potentially contribute to help solving the imminent global food crisis. However, research on insect-based foods (IBFs) has repeatedly pointed to the fact that, in many countries and cultures, negative attitudes towards eating insects are one of the most significant obstacles to promoting the consumption of IBFs. To date, only a small number of studies have investigated effective strategies to increase the acceptance of those foods. The research reported here focused on the role of celebrity endorsement, which is one of the most prevalent marketing strategies used to promote a wide range of products. We systematically explored whether and how such a strategy might affect the consumers' willingness to eat (WTE) IBFs. Our results provide the first demonstration that celebrities' perceived trustworthiness, knowledge about IBFs, and appropriateness (as an endorser of IBF products) are significant celebrity characteristics affecting people's WTE IBFs. We also found that celebrity type (i.e., actor/actress, musician, or athlete) interacts with participant gender in terms of their WTE IBFs. Namely, for male participants, IBF ads featuring actors/actresses or athletes were effective for increasing their WTE those foods. Meanwhile, for female participants, only actors/actresses significantly increased their WTE IBFs. Endorsement by a musician did not increase the WTE IBFs for either male or female respondents. Together, these findings demonstrate the celebrity endorsement as a prominent strategy to increase the WTE IBFs and reveal how and when the strategy is effective for promoting IBFs.